The intra- and inter-observer reliability of a novel protocol for two-point discrimination in individuals with chronic low back pain. (20th June 2016) - Ehrenbrusthoff, K; Ryan, C G; Grüneberg, C; Wolf, U; Krenz, D; Atkinson, G; Martin, D J
Abstract: Two-point discrimination is measured as an indicator of cortical reorganisation in musculoskeletal medicine. Nevertheless, data are lacking for the reliability of this measure in patients with non-specific chronic low back pain (NSCLBP). We aimed to quantify the intra- and inter-observer reliability of a novel protocol for measuring two-point discrimination in these patients. 35 participants (12 males, 23 females, mean age 52, SD 15 years) with NSCLBP were recruited. Three clinicians made 14 consecutive measurements of two-point discrimination with callipers. One of these clinicians repeated the assessment protocol within 7 d. During each measurement, the calliper width was widened in 5 mm increments until participants could consistently identify two points. Intra- and inter-observer agreement was quantified using mean difference, within-subject SD and limits of agreement (LOA). After using the first measurement for familiarisation, the mean of measurements 2–5 within an assessment resulted in the optimum compromise between clinic time constraints and acceptable intra-observer reliability; the within-subjects SD being 7.5 mm (LOA: 20.8 mm). Inter-observer reliability was generally poorer; requiring the mean of measurements 2–9 within an assessment for a similar within-subjects SD of 8.6 mm (LOA: 23.7 mm). It was estimated that these within-subjects SDs were small enough for a clinically-important change to be detected with a feasible sample size in future studies. The intra-observer reliability of our assessment protocol is acceptable for detecting a clinically relevant difference in two-point discrimination for future research purposes. Nevertheless, individual patient measurement variability is relatively high, especially between different clinicians.